Penilaian Kerusakan Jalan T. Panglima Nyak Makam Dengan Metode Bina Marga - Khalis, Muhammad; Silviana, Merry; Amalia, Amalia (Jurnal Teknik Sipil Unaya, 2025)
The aim of this research is to determine the effect of vehicle speed on the level of damage to the T. Panglima Nyak Makam road pavement with a length of 1000 meters for each segment length of 50 meters. The results of the analysis of the damage assessment of the T. Panglima Nyak Makam road using the Bina Marga Method showed that the overall level of damage was 604.50 m². The percentage of all damage is 11.57% of the total road area of 7000 m². 3. Meanwhile, for the vehicle speed survei on the T Panglima Nyak Makam road section along 1 km of the total road length of 1,891 km. Results in the average value of overall vehicle speed for light vehicles (LV) is 37.70 km/hour, for motorbikes (MC) is 34.57 km/hour. Based on these values, it can be concluded that the speed on the T Panglima road section Nyak Makam, with the classification of district/city roads with good road conditions, namely 30-50 km/hour.And also the results of road damage analysis based on the Bina Marga method show that the priority order for the T. Nyak Makam road is 9.75. Priority order 7 is a class A priority order, where roads in this priority order are included in the routine maintenance program. Routine monitoring and observation of damage is required.